Biplot Simulation of Length and Circumference of Different Body Regions of Swamp Buffalo (Bubalus bubalis) - Sampurna, I Putu; Nindhia, Tjokorda Sari; Werdi Susari, Ni Nyoman; Suatha, I Ketut (Journal of Buffalo Science, 2021)
Background: Biplot simulation using factor analysis with Promax kappa rotation of 90 is used to determine the coordinates of the length and body circumference dimensions of male and female mud buffalo in two-dimensional space. So that it can be known which body dimensions have fast, medium, and slow growth rates, and also to find out at what age male and female buffalo the growth rate is fast or slow. Methods: This study used 3 male and female buffaloes aged 10, 12, 14, 16, 18, and 20 months, so that the number of buffalo used was 36. The data obtained were analyzed using Factor Analysis with Promax Kappa 90 rotation. The object coordinates were the coordinates of male and female swamp buffalo aged 10, 12, 14, 16, 18, and 20 months, determined based on the Analysis Factor Scores Regression. The location of the coordinates of the length and circumference dimensions and the location of the object coordinates of male and female buffaloes aged 10, 12, 14, 16, 18, and 20 months are drawn using a biplot graph. Conclusion: The biplot simulation results show that the body dimensions in quadrant II have the fastest growth rate, namely the length of the horns and the length of the neck, which are body dimensions that are slow to reach adult size. The dimensions of the body in quadrant I are body length, head length, upper and lower neck circumference. While the slow growth rate in quadrant IV indicates that the dimensions of the body are already growing or the growth is not optimal; namely, the length of the ears and the length of the tail have reached adult size. At the same time, the abdominal circumference and chest circumference are due to their growth not being optimal. Based on age and sex, the dimensions of male buffalo's length and body circumference are always greater than that of female buffalo from the age of 10-20 months. The positional distance between male and female buffalo age shows that the older the age, the shorter the distance; this result indicates that the growth rate slows down with increasing age.